Tradisi Sebagai Sumber Penalaran Hukum Islam (Studi Paradigma Ahli Sunnah Wal Jama’ah): Tradisi Sebagai Sumber Penalaran Hukum Islam (Studi Paradigma Ahli Sunnah Wal Jama’ah) - hermanto, agus (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2017)
Abstract: "Tradition ('urf) as a Source of Islamic Law Reasoning; Study Paradigm Sunnah wal Jama'ah Experts in Developing Local Culture "One tradition ( 'urf) can be used as a source of Islamic law if it does not conflict with Personality', and not all traditions can be used as a source of Islamic law. Tradition itself is an activity that is repetitive, but does not violate the order of Shariah, the tradition is not sharia, but branches (furu ') in order to address or even develop Islamic teachings amaliyah (amaliy) or often called (bid’ah hasanah) .The ahlu sunnah wal jama'ah develop local culture such as tahlilan, yasinan, istighasah, tawashul or the like in the implementation of the (practice) there is no standard rules, but it is the implementation of more emphasis on reading tahlil (la ilaha ilallah), or yasinan namely reading yasin as the heart of a Qur'an, namely istighasah appeal help in Allah and not in others, and that is ihtiram tawashul to teachers as washilah in a prayer, and of course this is bid’ah hasanah not teaching out of Personality ' ,Keywords: Tradition, 'urf, Ahl Sunnah Wa al-Jama'ah